Highly Efficient and Thermally Stable K3AlF6:Mn4+ as a Red Phosphor for Ultra-High-Performance Warm White Light-Emitting Diodes - Song, Enhai; Wang, Jianqing; Shi, Jiahao; Deng, Tingting; Ye, Shi; Peng, Mingying; Wang, Jing; Wondraczek, Lothar; Zhang, Qinyuan (ACS Applied Materials and Interfaces, 2017)
Following pioneering work, solution-processable Mn4+-activated fluoride pigments, such as A2BF6 (A = Na, K, Rb, Cs; A2 = Ba, Zn; B = Si, Ge, Ti, Zr, Sn), have attracted considerable attention as highly promising red phosphors for warm white light-emitting diodes (W-LEDs). To date, these fluoride pigments have been synthesized via traditional chemical routes with HF solution. However, in addition to the possible dangers of hypertoxic HF, the uncontrolled precipitation of fluorides and the extensive processing steps produce large morphological variations, resulting in a wide variation in the LED performance of the resulting devices, which hampers their prospects for practical applications. Here, we demonstrate a prototype W-LED with K3AlF6:Mn4+ as the red light component via an efficient and water-processable cation-exchange green route. The prototype already shows an efficient luminous efficacy (LE) beyond 190 lm/W, along with an excellent color rendering index (Ra = 84) and a lower correlated color temperature (CCT = 3665 K). We find that the Mn4+ ions at the distorted octahedral sites in K3AlF6:Mn4+ can produce a high photoluminescence thermal and color stability, and higher quantum efficiency (QE) (internal QE (IQE) of 88% and external QE (EQE) of 50.6%.) that are in turn responsible for the realization of a high LE by the warm W-LEDs. Our findings indicate that the water-processed K3AlF6 may be a highly suitable candidate for fabricating high-performance warm W-LEDs.
CRIS-Team Scopus Importer:2023-04-20
Keywords: green route; luminous efficiency; red phosphor; ultrahigh performance; warm white LEDs